Blue Ocean Strategy: An investigation on Food Industry in the UAE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today's business environment is highly competitive and uncertain, forcing companies to continually adapt their strategies just to survive. The businesses that most people have grown up with are also facing tremendous changes; moreover, the pace of both reconstructions of business models, as well as the use of advanced technology, has increased.  Every step taken by businesses today is being questioned, therefore, it becomes challenging for many to keep up with new demands as well as sustaining in the market due to intense competition.The level of competition a business faces is an important indicator of its success in building its market share; indeed, the most reliable sign of success is when a firm no longer has any formidable competitors left in an existing market—this indicates true victory. Thus, in the light of dynamic markets and fierce competition, it has become customary for companies to continuously alter their business models and strategies. Over the years, many new business models have emerged, many of which have left their imprint. The Blue Ocean Strategy (BOS) is one such paradigm; created and published by W. Kim Chan and Renee Mauborgne, the book became an instantaneous success and was accepted all over the world.This study analyzes the applicability of the BOS in the context of Middle-East country; specifically, it investigates the impact of introducing the BOS in the UAE food industry and the channels of its action. To achieve this, the study first conducted an in-depth exploration of BOS, the tools and frameworks used to create a successful BOS, and the prevailing position of the food industry in the UAE. The study used qualitative data in the form of in-depth interviews to provide answers to the research questions.The preliminary findings indicate that applying the BOS model to the UAE food industry could lead to profit maximization and long term survival, therefore, firms are already exploring ways to apply the BOS to their respective operations. After analyzing the data, it was found that the BOS creates several opportunities for innovation and creativity.  The business can explore a new and uncontested market space with the help of the BOS if executed correctly. Applying the BOS for the first time does entail risks since the innovative idea needs to succeed in the market; therefore, success depends on the type of product offered.The study of the Blue Ocean Strategy is new and the applicability of the BOS to the food industry in the UAE has not been previously researched. Existing studies have tended to study both the BOS and food industry individually, but, the gap exists since no study has yet explored a combination of the two.  As a result, the ideas presented in this study could create an opportunity for future researchers to pursue research on various aspects of food and other related industries.